Діяльність на Буковині румунської поліції у міжвоєнний період. - Чучко, Михайло Костянтинович; Chuchko, Mykhailo (Краєзнавство. Науковий журнал. Київ, 2025. Вип.2 (129). С.155-169., 2025)
The annexation of Bukovina to Romania in the autumn of 1918 led to the transformation of local police agencies and their subsequent unification according to the model of the police of the old kingdom. In 1923, the police directorate in Chernivtsi was transformed into a police prefecture, and then reorganized into a regional police inspectorate. A police questura also operated in Chernivtsi. The main task of the Romanian police was to combat criminal offenses, conduct investigations and search for criminals, protect the existing state and social order, supervise the mood of the population in cities and villages, foreigners, the press and socio-political organizations. In addition, the police were involved in dispersing mass protests of a social and national nature. With the establishment of Soviet power in northern Bukovina in the summer of 1940, repressions began against the former employees of the Romanian police who remained in the region.
Activities of the Romanian police in Bukovina during the interwar period.
ЧНУ
Keywords: Буковина, Румунія, румунська поліція, міжвоєнний період, громадський порядок, кримінал, радянські репресії проти колишніх поліцейських.; Bukovina, Romania, Romanian police, interwar period, public order, crime, Soviet repressions against former police officers.